Expression of recombinant 35 kDa fragment of VP2 protein of canine parvovirus using Escherichia coli expression system - Inthong, Natnaree (Vet World, 2021)
BACKGROUND AND AIM: Canine parvovirus (CPV) is one of the most common viral infections in dogs, causing acute hemorrhagic gastroenteritis and high mortality. Vaccination effectively prevents CPV infection. However, the currently available CPV vaccines have concerns such as maternal immunity interference, shedding of virus vaccine, and false-positive result based on polymerase chain reaction after vaccination. A subunit vaccine can overcome these problems. This study aimed to express the recombinant 35 kDa fragment of the VP2 protein (consisting of epitopes 1-7) and the recombinant full-length VP2 protein (consisting of epitopes 1-10) and to study the ability of these two recombinant proteins to react with rabbit anti-CPV polyclonal antibodies. MATERIALS AND METHODS: The full length and 35 kDa fragment of VP2 gene of CPV were cloned into the pBAD202 Directional TOPO(™) expression vector and expressed in E. coli. The recombinant full-length and the recombinant 35 kDa fragment proteins of VP2 were analyzed using sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blotting. RESULTS: The recombinant full-length and the recombinant 35 kDa fragment VP2 genes were successfully cloned and expressed. The optimum concentrations of arabinose and induction time for the recombinant full-length and the recombinant 35 kDa fragment VP2 proteins were 0.2% for 6 h and 0.02% for 6 h, respectively. The recombinant full-length and the recombinant 35 kDa fragment VP2 protein molecular weights were approximately 81 and 51 kDa, respectively. The recombinant full-length and the recombinant 35 kDa fragment VP2 proteins specifically interacted with rabbit anti-CPV polyclonal antibodies. CONCLUSION: These results suggest that the recombinant 35 kDa fragment and the recombinant full-length VP2 proteins may be useful in developing a CPV diagnostic test or vaccine.